ANALISA NILAI KEKASARAN PERMUKAAN MATERIAL BAJA ST 41 PADA PROSES PEMESINAN BUBUT CNC DENGAN METODE TAGUCHI - ibnu salikin; Eko Yudo; Idiar (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The machining process used in the production process is a machining process that must be in accordance with the demands of the production. Where the level of precision, accuracy, quality and quantity of a product is the main thing in the machining process. to obtain a minimum response to the surface roughness of the workpiece. The research that has been tried aims to ensure the contribution of the parameters to the CNC MORI SEIKI SL-25 machining process to reduce the alteration of the workpiece surface roughness reaction simultaneously. As well as setting the right parameters of the CNC MORI SEIKI SL-25 machining process parameters in order to obtain a minimum workpiece surface roughness. The machining process parameters that were varied were cutting speed, feed depth and feed motion. The purpose of this study was to determine the surface roughness of carbon steel. This study uses parameters that affect the shape of the surface roughness value of St 41 material, namely cutting speed (110 m/min, 120 m/min, 150 m/min), depth level (0.5 mm, 0.8 mm, 1 mm)) and feeding speed (0.15mm/put, 0.925mm/put, 0.35mm/put). The value of the surface roughness of the St 41y material, which is the percent cutting speed, has a value of 11.06%, the infeed depth has a value of 0.19%. And eating motion has the smallest value of -20.97%.